2006
DOI: 10.1191/135248506ms1251oa
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of Th1, monocyte/macrophage and Th2 cytokine mixtures on early gene expression for immune-related molecules by central nervous system mixed glial cell cultures

Abstract: Cytokines secreted within the central nervous system (CNS) are important in the development of multiple sclerosis (MS) lesions. The balance between Th1, monocyte/macrophage (M/M) and Th2 cytokines in the CNS may be pivotal in determining the outcome of lesion development. We examined the effects of mixtures of cytokines on gene expression by CNS glial cells, as mixtures of cytokines are present in MS lesions, which in turn contain mixtures of glial cells. In this initial analysis by gene array, we examined cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 192 publications
1
59
0
Order By: Relevance
“…Similar concentrations have been used in numerous in vitro studies, including ours [9][10][11]33], with effects on gene expression and cell function in many cell types. The physiologic relevance of the cytokine concentrations used in vitro can be debated.…”
Section: Protective Effects Of Cytokinesmentioning
confidence: 95%
See 3 more Smart Citations
“…Similar concentrations have been used in numerous in vitro studies, including ours [9][10][11]33], with effects on gene expression and cell function in many cell types. The physiologic relevance of the cytokine concentrations used in vitro can be debated.…”
Section: Protective Effects Of Cytokinesmentioning
confidence: 95%
“…We previously reported that these mixtures of cytokines induced a large number of changes in gene expression at 6 h in these mixed glial cultures, with each mixture giving a unique pattern of changes [9][10][11]. As expected, the Th1 and M/M cytokine mixtures upregulated a number of glial genes for cytokines, chemokines and their receptors considered to be pro-inflammatory, while the Th2 mixture downregulated many of these same genes [9]. In addition, Th2 cytokines upregulated the gene for the neurotrophin BDNF [10], a change subsequently confirmed at later time points by PCR (unpublished data).…”
Section: Protective Effects Of Cytokinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytokines produced by T cells strongly influence glial activation and induce various genes in glial cells, providing, for example in microglia, to present a pro-inflammatory or anti-inflammatory phenotype. [14,15]. The interaction between T cells and glial appears to mediate one of the main mechanisms of neuroprotective immunity.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 98%